Operational research as a mechanism to improve treatment outcomes for drug-resistant TB in the WHO European Region - G.B. Migliori; O. Korotych; J. Achar; A. Ciobanu; G. Dravniece; M. Germanovych; E. Gurbanova; A. Hovhannesyan; N. Khachatryan; L. Kuksa; N. Lomtadze; M.L. Rich; et al. (IJTLD Open)
In 2022, the WHO European Region accounted for 15.1% of all incident rifampicin-resistant/multidrug-resistant TB (RR/MDR-TB) cases. Most occurred in 18 high-priority countries of eastern Europe and central Asia, many of which joined an initiative led by the WHO Regional Office for Europe. The aim was to introduce three, fully oral, 9-month modified shorter treatment regimens (mSTR) to treat RR/MDR-TB under operational research conditions. The three regimens were: 1) bedaquiline + linezolid + levofloxacin + clofazimine + cycloserine (BdqLzdLfxCfzCs); 2) BdqLzdLfxCfz + delamanid (Dlm) for children over 6 years of age and adults; and 3) DlmLzdLfxCfz for children under 6 years of age. The project aimed to enhance treatment success, facilitate mSTR implementation, promote quality of care and build research capacity, while also contributing to global knowledge on all-oral mSTR use. Between April 2020 and June 2022, >2,800 patients underwent mSTR treatment in the WHO European Region. This unique experience promoted further collaboration with national tuberculosis programmes, health authorities, experts and donors within and outside Europe, with a focus on implementing operational research and improving the quality of care in high TB burden countries of the region. In the hope of encouraging others to adopt this model, we have described the principles of the initiative, its strengths and weaknesses and next steps.